131 Perioperative Management of Warfarin on Surgical Wards at District General Hospital. (12th October 2021) - Artyushina, A; Norton, E; Pathan, A; Sen, R
Abstract: Introduction: Many patients admitted to surgical wards are on warfarin. Poor knowledge of guidelines regarding reversal and restarting of anticoagulant medications can delay surgery, lead to poor outcomes and delay the discharge of patients. The aim of this audit was to establish whether junior doctors are confident in managing warfarin according to local guidelines and to improve their knowledge and confidence. Method: A questionnaire was used to assess confidence of junior doctors currently working in general surgical departments. An educational poster was placed in the junior doctors' office and the questionnaire was repeated. We then conducted a teaching session on the perioperative management of warfarin and repeated the questionnaire again. Results: Confidence in reversing and restarting warfarin was significantly higher following the teaching session (p = 0.017 and p < 0.001 respectively). No significant difference was seen following the introduction of educational posters. Confidence in applying the guidelines on perioperative warfarin management was significantly higher following the teaching session (p < 0.001 ). Following the introduction of educational posters and the formal teaching session doctors felt they knew better how to access the guidelines (not statistically significant for either guideline) and referred to them more (p = 0.0178 for warfarin reversing and p = 0.0940 for warfarin restarting guideline). Conclusions: Having doctors who are confident in managing warfarin is crucial to avoid delays in treatment and discharge. This audit showed that a teaching session indeed improved doctors' knowledge and confidence. Regular formal teaching is essential, and a repeat audit is planned to be performed during the next rotation.